Source of medicines and medicine information by self-reported persons living with hy-pertension and diabetes in rural and urban Ghana - Opare-Addo MN; Buabeng KO; Marfo AF; Osei FA; Owusu-Dabo E; Ansong D; Anto BP; Boaheng JM; Nyanor I. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objectives: This study was conducted to determine the source of medicines and medicine information of persons living with hypertension and diabetes in rural and urban Ghana and assessing if they are influenced by predisposing and enabling factors as defined by Andersen's behavioural model. Methods: A population based cross sectional study was conducted in four (4) rural and four (4) urban districts in the Ashanti Region of Ghana. A multistage and proportional sampling method was used in enrolling participants aged 18 years and above. A pre-tested structured questionnaire was used to collect primary data from respondents. Data collected was exported to STATA for analysis. Descriptive analysis was performed. Chi-square tests/Fisher's exact test and multinomial logistic regression models were used to establish association between variables. Results: A total of 336 self -reported persons with hypertension and diabetes were enrolled in the study with 199(59.23%) living in urban communities. The majority of participants with hypertension and diabetes living in the rural communities 77 (56.20%) were females contrasting with the male majority in urban communities 106 (53. 27%). In the rural communities, 49 (35.77%) of participants sourced medicines from the health centre while 45 (32.85%) and 35(25.55%) sourced medicines from the hospital and over the counter medicine shop (OTCMS) respectively. In the urban communities, 153 (76.88%) sourced medicines from the hospital while 33 (16.58%) sourced medicines from the pharmacy. The predisposing factor age (OR: 1.1, 95%CI 1.040-1.210) under OTCMS, age (OR 1.0, 95%CI: 1.002-1.066) under hospital and enabling factor socioeconomic status (OR: 0.3, 95%CI 0.085-0.855) under Hospital influenced participant's source of medicine in the urban communities. The results also revealed that majority of participants in both rural 99 (72.26%), and urban 164 (82.41%) communities sourced medicine information mainly from public healthcare facilities, pre-disposing factors; age (OR 1.1 95%CI 1.032-1.270) under family member, age (OR 1.1, 95%CI 1.022-1.167) under friend health professional, age (OR 1.1, 95%CI 1.050-1.147) under nearest health institution, marital status (OR: 0.004, 95%CI 0.003-0.441) under friend health Professional were found to influence participants' source of medicine information in the urban communities while in the rural communities the predisposing factor marital status (OR 10.6, 95%CI 1.044 -106.835), education (OR: 26.1, 95%CI 1.271-537.279) under friend health professional, age (OR 1.1, 95%CI 1.002-1.187), educational level (OR 30.6, 95%CI 1.718-546.668) under nearest health institution and enabling factor socio-economic status (OR 6.6, 95%CI 1.016 -43.510) under nearest health institution influenced one's source of medicine information. Conclusions: Majority of inhabitants with hypertension and diabetes in both rural and urban communities, sourced medicines and medicine information from public health institutions though a larger proportion was recorded in the urban communities. More participants in the rural communities than in the urban communities sourced medicines and medicine information from community pharmacies. Participants' source of medicine and medicine information was influenced by both predisposing and enabling factors.